Hydrothermal synthesis of nanostructured V2O5 material for photocatalytic applications: Effect of surfactants - Do, Quang Dat; Chu, Manh Hung; Nguyen, Van Duy; Lam, Van Nang; Vo, Thi Lan Phuong; Le, Thi Minh Ngoc; Tran, Ngoc Tu; Pham, Thi Nga; Nguyen, Thiet Ke; Lai, Van Duy; Nguyen, Duc Hoa (JST: Engineering And Technology For Sustainable Development, 2023)
In this study, the nanostructured V2O5 photocatalyst was prepared by a hydrothermal process followed by calcination with the addition of various surfactants to the precursor solution. The properties of the formed V2O5 nanomaterials were investigated by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and ultraviolet-visible spectroscopy (UV-Vis). The SEM images and XRD spectra showed that the V2O5 nanostructures with different morphologies crystallized in the orthorhombic phase were successfully synthesized. The FTIR spectrum gives characteristic oscillations of the chemical bonds in V2O5, containing the V-O-V vibration. The UV-Vis spectrum determines the band gap energy in accordance with the bandgap energy value of V2O5. In particular, the results demonstrated that the addition of surfactant had a strong effect on the morphology, band gap energy and surface chemistry of the photocatalysts. The comparison between the addition of the three surfactants (SDS, P123, CTAB) showed that the addition of SDS produced the most efficient V2O5 photocatalyst is beneficial to improve V2O5 agglomeration. Under the illumination of the Compact lamp, the V2O5 product using SDS removal could reach up to 90% Methylene Blue solution after 120 minutes.